2018
DOI: 10.1103/physrevx.8.021048
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap and Fermi-Surface Topology in the Two-Dimensional Hubbard Model

Abstract: One of the distinctive features of hole-doped cuprate superconductors is the onset of a "pseudogap" below a temperature T Ã . Recent experiments suggest that there may be a connection between the existence of the pseudogap and the topology of the Fermi surface. Here, we address this issue by studying the twodimensional Hubbard model with two distinct numerical methods. We find that the pseudogap only exists when the Fermi surface is holelike and that, for a broad range of parameters, its opening is concomitant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
122
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 87 publications
21
122
1
1
Order By: Relevance
“…The arrangement of currents in [31] and in the d-density wave order parameter [32]. The same symmetries and the same problems should occur with generation of Fermi-surfaces through alternating antiferromagnetic order or antiferromagnetic order with gauge-field fluctuations [33][34][35]. The multitudinous Fermi-surfaces generated with charge density waves with various periods have been well documented [5].…”
Section: Hamiltonian In Momentum Basismentioning
confidence: 99%
See 1 more Smart Citation
“…The arrangement of currents in [31] and in the d-density wave order parameter [32]. The same symmetries and the same problems should occur with generation of Fermi-surfaces through alternating antiferromagnetic order or antiferromagnetic order with gauge-field fluctuations [33][34][35]. The multitudinous Fermi-surfaces generated with charge density waves with various periods have been well documented [5].…”
Section: Hamiltonian In Momentum Basismentioning
confidence: 99%
“…Calculations for the pseudogap have mostly followed the idea of antiferromagnetism or antiferromagnetic fluctuations [34] or mathematically related idea of d-wave density order [32] or fluctuations of gauge fields by themselves [31] or coupled to antiferromagnetism [35]. They all have the problem of several Fermi-surfaces or no Fermi-arc or both.…”
Section: Earlier Theories For the Pseudogapmentioning
confidence: 99%
“…On the other hand, it has been proposed that the pseudogap can emerge upon doping the Mott insulator without invoking broken symmetry states: Mott localisation and short-range antiferromagnetic correlations form singlet bonds that open a pseudgap [8], whose onset is marked by crossovers in thermodynamic quantities [1,9]. From a theoretical perspective, over the years the numerical solutions of the two-dimensional Hubbard model relevant for these systems support the idea that pseudogap originates from strong correlations [10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…The hole-doped copper-oxide superconductors have a peculiar phase of the pseudogap at underdoping and temperatures above T c . CDMFT studies have shown that its opening can be related to a topological Lifshitz transition at that the Fermi surface turns from electron-to holelike 59,60 . It can be defined as the point at that the renormalized quasiparticle energy of the K = X/Y points…”
Section: Spectral Properties and Doping Dependencementioning
confidence: 99%